A modified damage accumulation model for life prediction of aero‐engine materials under combined high and low cycle fatigue loading. Issue 11 (23rd August 2021) - Bai, Song; Huang, Hong‐Zhong; Li, Yan‐Feng; Yu, Aodi; Deng, Zhiming
Abstract: Aero‐engine hot section components experience combined high and low cycle fatigue (CCF) loading under actual working conditions. This paper proposes a modified fatigue damage accumulation model to precisely predict lifetimes of aero‐engine materials according to the newly presented interaction factor, which is able to quantitatively map damage interactions introduced by high cycle fatigue (HCF) and low cycle fatigue (LCF) loads. With the model, the lifetimes of four typical engine materials are predicted and compared to their factual data from experiments. The validation of the model is illustrated by a comprehensive comparison of the results concluded by the proposed model and that of other classical methodologies, which indicates that the new model holds the best performance in lifetime predictions. Moreover, an actual engineering case, which is the lifetime prediction of third stage turbine blades of an aero‐engine, is completed to validate the feasibility of the proposed method.